Wilckodontics-an interdisciplinary periodontics-orthodontic approach to accelerate orthodontic treatment time: a literature review: Wilckodontics-sebuah pendekatan interdisiplin periodontik-ortodontik untuk mempercepat waktu perawatan ortodontik: tinjauan pustaka - Shinta Rahma Mansyur; Mardiana Andi Adam (Makassar Dental Journal, 2022)
Objective: Orthodontic treatment is the longest dental procedure performed. To accelerate tooth movement, orthodontists and periodontists have developed a new technique, termed Wilckodontics or periodontal accelerated osteogenic orthodontics. This technique combines selective alveolar corticotomy techniques, particulate bone grafts, and orthodontic force. This review aims to discuss the concepts and technique of Wilckodontics as a combination of interdisciplinary treatment. Methods: An internet-based search was conducted to identify various literatures discussing Wilckodontics using several keywords. Results: Wilcko-dontics can accelerate tooth movement in adult patients and shorten treatment time. Compared with conventional orthodontic treatment, this technique shows advantages in terms of treatment cycle and treatment effect. In addition, the Wilckodontics does not increase the risk of root resorption, periodontium injury, and alveolar bone defects. Conclusion: Wilckodontics re-quires various diagnostic parameters and modification of the procedure. With the right synergy of orthodontist and periodon-tist, successful treatment can be achieved.